Intra- and interspecific genetic diversity of New Zealand hairworms (Nematomorpha). Issue 8 (9th March 2017) - TOBIAS, ZACHARY J. C.; YADAV, ARUN K.; SCHMIDT-RHAESA, ANDREAS; POULIN, ROBERT
SUMMARY: Hairworms (Nematomorpha) are a little-known group of parasites, and despite having been represented in the taxonomic literature for over a century, the implementation of molecular genetics in studies of hairworm ecology and evolution lags behind that of other parasitic taxa. In this study, we characterize the genetic diversity of the New Zealand nematomorph fauna and test for genetic structure within the most widespread species found. We provide new mitochondrial and nuclear ribosomal sequence data for three previously described species from New Zealand: Gordius paranensis, Parachordodes diblastus and Euchordodes nigromaculatus . We also present genetic data on a previously reported but undescribed Gordius sp., as well as data from specimens of a new Gordionus sp., a genus new for New Zealand. Phylogenetic analyses of CO1 and nuclear rDNA regions correspond with morphological classification based on scanning electron microscopy, and demonstrate paraphyly of the genus Gordionus and the potential for cryptic species within G. paranensis . Population-level analyses of E. nigromaculatus showed no genetic differentiation among sampling locations across the study area, in contrast to previously observed patterns in known and likely definitive hosts. Taken together, this raises the possibility that factors such as definitive host specificity, intermediate host movement, and passive dispersal of eggs and larvae may influence host–parasite population co-structure in hairworms.